1987
DOI: 10.1161/01.hyp.9.4.332
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against a pressor role for vasopressin in spontaneous hypertension.

Abstract: Received May 12, 1986; accepted October 6, 1986. to WKY, 1 ' 2 and at 5 and 8 weeks of age VP release is exaggerated in SHR relative to WKY in response to a decrease in plasma volume in vivo 3 or following exposure of the hypothalamoneurohypophyseal system to acetylcholine and angiotensin II in vitro. 4 ' 5 Thus, increased secretion of VP in response to selected stimuli may underlie the elevation of plasma and urinary VP in SHR.Peripheral resistance is elevated in SHR, 6 ' 7 and this elevation is thought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…This pure V 1 R vascular antagonist profile is of importance when one considers the "ideal" profile of a AVP antagonist to be developed as an antihypertensive agent. Based on the elegant studies performed by Sladek et al 7,33 with peptide antagonists in the spontaneously hypertensive rat, a pure V 1 R antagonist is not expected to produce a sustained decrease in blood pressure, whereas a mixed V 1 /V 2 R antagonist will achieve a reduction in blood pressure via alterations of both peripheral resistances and circulating blood volume. However, the effective and safe ratio of V 1 /V 2 R antagonism remains to be established because of the study by Hofbauer et al, 34 who observed in DOCA-salt hypertensive rats that the administration of a mixed V 1 /V 2 R peptide antagonist led to a greater blood pressure reduction than a pure V 1 R antagonist although at the expense of water loss and hypernatremia.…”
Section: Discussionmentioning
confidence: 99%
“…This pure V 1 R vascular antagonist profile is of importance when one considers the "ideal" profile of a AVP antagonist to be developed as an antihypertensive agent. Based on the elegant studies performed by Sladek et al 7,33 with peptide antagonists in the spontaneously hypertensive rat, a pure V 1 R antagonist is not expected to produce a sustained decrease in blood pressure, whereas a mixed V 1 /V 2 R antagonist will achieve a reduction in blood pressure via alterations of both peripheral resistances and circulating blood volume. However, the effective and safe ratio of V 1 /V 2 R antagonism remains to be established because of the study by Hofbauer et al, 34 who observed in DOCA-salt hypertensive rats that the administration of a mixed V 1 /V 2 R peptide antagonist led to a greater blood pressure reduction than a pure V 1 R antagonist although at the expense of water loss and hypernatremia.…”
Section: Discussionmentioning
confidence: 99%
“…A role for VP in spontaneous hypertension was supported by early studies in which injection of a VP antiserum lowered blood pressure in strokeprone SHR, 8 but studies employing short-term administration 3 or long-term infusion of a specific antagonist of the vascular effects of VP, d(CH2) 3 Tyr(Me)arginine vasopressin (AVP), 9 suggested that the vasoconstrictor action of VP was not an important component of the hypertension in SHR. Shortterm administration of the antagonist to 11-weekold SHR resulted in a small decrease in mean arterial pressure (9 ± 1 mm Hg), 3 but long-term infusion of the antagonist from 4 to 12 weeks of age at rates that blocked the pressor actions of VP did not alter the course of systolic hypertension.…”
mentioning
confidence: 99%
“…Shortterm administration of the antagonist to 11-weekold SHR resulted in a small decrease in mean arterial pressure (9 ± 1 mm Hg), 3 but long-term infusion of the antagonist from 4 to 12 weeks of age at rates that blocked the pressor actions of VP did not alter the course of systolic hypertension. 9 This vascular antagonist has weak antidiuretic agonist properties (0.3 vs 323 U/mg for VP). Thus, the failure to obtain antihypertensive effects with this antagonist comparable to those reported with VP antiserum could have reflected the opposite action of the VP analogue and the VP antiserum on the renal action of VP.…”
mentioning
confidence: 99%
“…Some studies have concluded that vasopressin is not a vital hormone for the onset and maintenance of hypertension in SHR (19,20). Okada et al (9) reported that the V1A is rarely effective in lowering AP in intact SHR.…”
Section: Discussionmentioning
confidence: 99%
“…3, the plasma concentration of AVP was significantly greater in BHR than in NCR (n 5 each, p 0.05) at baseline, and it was significantly increased by ganglionic blockade (AVPBHR 1.60 0. 20 …”
Section: Plasma Concentrations Of Avpmentioning
confidence: 99%